Social Media Users' Reactions to Suicide. Issue 8 (17th September 2022) - Al-Zaman, Md. Sayeed; Or Rashid, Mohammad Harun
Abstract: To explore how social media users react to suicide, we collected and analyzed 3, 482 public comments on Bangladeshi suicide news emphasizing the user's gender, victim's gender, victim's profession, and suicide risk factor. The quantitative content analysis found that users react to suicide in nine different ways: angry, sadness, surprise, irony, ridicule, judgmental, justification, speculation, and miscellaneous. Of them, angry (20.3%) is the dominant reaction. In many cases, users mock the suicide victims (12.7%), showing less empathy. We found strong positive correlations between users' reactions and victims' profession ( φ = 0.493; p < .05) and users' reactions and suicide risk factors ( φ = 0.233; p < .05).